2022
DOI: 10.1371/journal.pone.0271027
|View full text |Cite
|
Sign up to set email alerts
|

Divergent confidence intervals among pre-specified analyses in the HiSTORIC stepped wedge trial: An exploratory post-hoc investigation

Abstract: Background The high-sensitivity cardiac troponin on presentation to rule out myocardial infarction (HiSTORIC) study was a stepped-wedge cluster randomised trial with long before-and-after periods, involving seven hospitals across Scotland. Results were divergent for the binary safety endpoint (type 1 or type 4b myocardial infarction or cardiac death) across certain pre-specified analyses, which warranted further investigation. In particular, the calendar-matched analysis produced an odds ratio in the opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…17 A post-hoc investigation that included comparing time from study start as a cubic spline, categorical variable and as a random variable, found very little influence compared with using time as a simple linear fixed effect variable. 34 Nevertheless, having time as fixed effect assumes a similar linear trend in all hospitals, which may have been the case in the Anand study, but may not be the case in this study. Therefore, we will not finalise the model until after comparing several options, using a simulated intervention and LOS data from a period preceding the present study.…”
Section: Open Accessmentioning
confidence: 83%
“…17 A post-hoc investigation that included comparing time from study start as a cubic spline, categorical variable and as a random variable, found very little influence compared with using time as a simple linear fixed effect variable. 34 Nevertheless, having time as fixed effect assumes a similar linear trend in all hospitals, which may have been the case in the Anand study, but may not be the case in this study. Therefore, we will not finalise the model until after comparing several options, using a simulated intervention and LOS data from a period preceding the present study.…”
Section: Open Accessmentioning
confidence: 83%